Reflection on the occupational risks that the nursing team may be exposed to: A literature review (Research, Society and Development, 2021)
The health of workers, especially those working in the health area, such as the nursing team, are important and essential pieces for life within society, the health agencies, along with their teams that are on the front lines, need to provide good working conditions for this population. The issue in question is to discover the occupational risks that health professionals are exposed to during the working day. In this sense, the objective of this study was to analyze and discuss occupational risks that health professionals are exposed to during their working hours. The research consists of a literature review, with relevant information being combined with the Virtual Health Library (VHL), Latin American Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SCIELO) Medline. The main results found could show the risks that health professionals are exposed to in the workplace, that is, these professionals are subject to acquiring or developing physical, chemical, biological, ergonomic, and accident-related illnesses. It is clear that workers who work in the hospital environment deal daily with daily exposure to disease-causing agents. Therefore, nursing professionals end up being the most affected public, and consequently the one with the greatest chances of acquiring specific work-related illnesses, as they are the professionals who deal with patients on a daily basis.